"Farmers Don't Dance": The Construction of Gender in a Rural Scottish School. Issue 1 (1st March 2020) - Menzies, Fiona G.; Santoro, Ninetta
Abstract: In this article we examine the influence of rurality on the construction of masculinity and femininity for, and by, pupils in a rural secondary school in Scotland. Using data from semi-structured interviews with male and female pupils and a teacher, as well as observations of classroom interactions over a period of 12 months, we highlight how girls take up multiple and complex gendered identities in a rural context and we emphasize the tensions they experience as they negotiate a feminine identity in a rural space constructed and described as masculine. Findings suggest that this construction is, at times, supported by teachers' practices and their interactions with pupils. We conclude by discussing the implications for teachers in rural schools and point to the need to support girls to ensure that their educational opportunities are not limited by the deep-rooted associations that exist between rurality and masculinity.